COMPARISON OF DIFFERENT PHENOYPIC TESTS FOR IDENTIFICATION OF CANDIDA ISOLATED FROM ORAL CAVITY - Hooli, Amruta B.; Bhat, Kishore G.; Ingalgi, Preeti (International Journal of Research -GRANTHAALAYAH, 2020)
Background and Objectives: Oral candidiasis is one of the most common fungal infections affecting the oral mucosa. Candida genus is comprised of numerous species amongst which C.albicans is the commonest followed by C. dubliniensis. Interest has been increased towards identifying the non-albicans resistant to antifungal drugs. Various techniques are developed for species identification such as traditional, rapid, molecular and automated methods. These methods have their own advantages and limitations. Though the traditional methods are complex, time consuming, they are simple and economical as well. Hence this study was conducted to compare the different methods for presumptive species identification. Method: A total of 50 strains were isolated from patients suffering from oral candidiasis. Samples were collected from the affected area and transferred to sterile PBS. Each sample was subjected for germ tube test, lipolytic activity, chrome agar, check for chlamydsopore formation and carbohydrate assimilation test. Results: In the present study the phenotypic tests could provisionally identify the species. Out of 50 strains 27 isolates were identified by germ tube test, 36 strains produced lipase and positive for lipolytic activity. Chlamydospore formation provided a definitive identification of only 17 isolates. Only 7 isolates showed positive for carbohydrate assimilation tests. Conclusion: Our study clearly showed that the phenotypic methods are useful for only presumptive identification hence the molecular methods have to be performed for definitive identification.